An Introduction to Cyber Analysis and Targeting - Couretas, Jerry M. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a comprehensive view of cyber operations, analysis and targeting, including operational examples viewed through a lens of conceptual models available in current technical and policy literature. Readers will gain a better understanding of how the current cyber environment developed, as well as how to describe it for future defense. The author describes cyber analysis first as a conceptual model, based on well-known operations that span from media to suspected critical infrastructure threats. He then treats the topic as an analytical problem, approached through subject matter interviews, case studies and modeled examples that provide the reader with a framework for the problem, developing metrics and proposing realistic courses of action. Provides first book to offer comprehensive coverage of cyber operations, analysis and targeting; Pulls together the various threads that make up current cyber issues, including information operations to confidentiality, integrity and availability attacks; Uses a graphical, model based, approach to describe as a coherent whole the development of cyber operations policy and leverage frameworks; Provides a method for contextualizing and understanding cyber operations.
1-Cyber Analysis and Targeting -- 2-Cyber Policy, Doctrine and Tactics, Techniques and Procedures (TTPs) -- 3-A Taxonomy of Cyber Threats -- 4-Cyber Influence Operations -- 5-Cyber ISR and Analysis -- 6-Cyber Security and Defense for Analysis and Targeting -- 7-Cyber Offense and Targeting -- 8-Cyber Systems Design -- 9-Measures of Cyber Performance and Effectiveness -- 10-Cyber Modeling and Simulation for Analysis and Targeting -- 11-Cyber Case Studies -- 12-Cyberspace Analysis and Targeting Conclusion.
Keywords: Cooperating objects (Computer systems).; Signal processing; Telecommunication; Cyber-Physical Systems; Digital and Analog Signal Processing; Communications Engineering, Networks